(untitled) (Annual of the Faculty of Philosophy in Skopje, 2010)
Attaining coordination in the security sector is one of the key issues in the Republic of Montenegro. It emerges from the interdependence of components of the institutions and of the extent of interdependence of people in the very institutions and bodies. Thus, coordination is the key element in the work of different public order services and security and intelligence services. Lack of coordination often leads to duplication of activities and the greatest risk is the probability for misinformation of state institutions for issues concerning national security. Practice in the Montenegro shows that the coordination function is more successful where there are modern subjects with experience, where the activities are executed according to certain plans, and previously determined schedule. Contrary, at subjects without experience, coordination function is more difficult, inconsistent and with no viable results.